Survey of Comparative Frequency, Severity and Level of Conflict in ICU nurses in Academic and Non- Academic hospitals in Yazd,1390 - Atashzashzadeh shoorideh, Forozan; Esmaeelzadeh, Somayeh; Zagheri Tafreshi, Mansoreh; Alavi Majd, Hamid; Abed Saeedi, Zhila (Advances in Nursing & Midwifery, 2013)
Abstract Introduction and Aim: Conflict is inevitable phenomena in man’s life and daily communication. This study intended to assessment of frequency, intensity and level of conflict in nursing in academic and non- academic hospitals in Yazd. Materials: In this comparative descriptive study, ICU nurses in academic and non-academic hospitals in Yazd were selected. Instrument of data collection was questionnaire. Data were analysis by SPSS and descriptive and analytical statistic. Findings: Non- nursing task in intra-group conflict in academic and non-academic hospitals has more frequency, intensity and level. In intra-group conflict, mean level of a sense of competition in order to maintain position, was high. In inter-group conflict, lack of cooperation wards with ICU showed more frequency, intensity and level in academic hospitals. However, in non-academic hospitals, personnel turnover has more intensity. In conflict of group and patient family, insist of family on staying in the bedside in academic and non-academic hospitals have more frequency, intensity and level. Comparing three domain of conflict showed intra-group conflict in academic and non-academic hospitals has more frequency and intensity of the conflict. But, level of conflict between group and patient’s family has more. Frequency, intensity, and level of ICU nurses were average. Conclusion: Findings showed that recognizing and understanding the cause of conflict can be prevented from incidence and by property managing, can be used from positive effects of conflict. Keyword: Conflict, Conflict risk factors, Nurses, ICU